2004
DOI: 10.1080/01926230490465865
|View full text |Cite
|
Sign up to set email alerts
|

Results of Chronic Dietary Toxicity Studies of High Viscosity (P70H and P100H) White Mineral Oils in Fischer 344 Rats

Abstract: Two-year dietary studies were conducted to determine the chronic toxicity and its reversibility, and the carcinogenicity of P70(H) and P100(H) white mineral oils in Fischer-344 rats (F-344). The studies were identical in design and followed the Organization for Economic Cooperation and Development, Guidelines for Testing Chemicals, Guideline 453, 1981. Additional endpoints evaluated were: (1) extent of mineral hydrocarbon deposition in liver, kidneys, mesenteric lymph nodes, and spleen of female rats at 3, 6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 15 publications
4
42
1
Order By: Relevance
“…The most common tumour types were mononuclear leukemia and pituitary/pars distalis adenoma (tumour incidences reported in Table 18). Table 18: Tumour incidences in rats exposed to P70(H) and P100(H) (Trimmer et al, 2004 The incidences of mononuclear leukemia in female rats at 240 mg/kg P70(H) and of pituitary/pars distalis adenoma in high dose females (1200 mg/kg) receiving P100(H) were within the respective historical control ranges for the strain of rat used and are considered incidental, and not treatment related.…”
Section: Mixturesmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common tumour types were mononuclear leukemia and pituitary/pars distalis adenoma (tumour incidences reported in Table 18). Table 18: Tumour incidences in rats exposed to P70(H) and P100(H) (Trimmer et al, 2004 The incidences of mononuclear leukemia in female rats at 240 mg/kg P70(H) and of pituitary/pars distalis adenoma in high dose females (1200 mg/kg) receiving P100(H) were within the respective historical control ranges for the strain of rat used and are considered incidental, and not treatment related.…”
Section: Mixturesmentioning
confidence: 99%
“…In the liver, however, the microgranulomas were surrounded by inflammatory cells. Evidence from a two year carcinogenicity study on two high viscosity mixtures (P70(H) and P100(H)) suggest that the microgranulomas in liver and MLN do not cause a prolonged inflammatory response or other severe pathological changes following chronic exposure in Fischer rats (Trimmer et al, 2004). However, the CONTAM Panel concluded that it would be prudent to assume that liver microgranulomas, observed in the Fischer 344 rats, could be potentially relevant to humans and therefore the critical effect for the risk assessment of MOSH.…”
Section: Moahmentioning
confidence: 99%
See 2 more Smart Citations
“…Trimmer et al (2004) assessed long-term toxicity and carcinogenicity of two mineral oils: a medium viscosity mineral oil (kinematic medium 8.97 mm²/s at 100 °C) and a high viscosity mineral oil (kinematic viscosity 11 mm²/s at 100 °C) in a 2-year study, conducted in male and female F344 rats.…”
Section: Chronic Toxicity and Carcinogenicitymentioning
confidence: 99%